How Far Can You Go?

Find the sum of all positive integers n n such that there exists p N p\in \mathbb{N} that satisfies the divisibility

p n 1 + ( p + 2 ) n 1 p n + ( p + 2 ) n . p^{n-1}+(p+2)^{n-1}\mid p^n+(p+2)^n.

This problem is a generalization by me of a problem that appeared in St. Petersburg City Mathematical Olympiad 1996.


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Daniel Liu
Aug 15, 2014

Note that p n + ( p + 2 ) n = ( p + 1 ) ( p n 1 + ( p + 2 ) n 1 ) + ( ( p + 2 ) n 1 p n 1 ) p^n+(p+2)^n=(p+1)(p^{n-1}+(p+2)^{n-1})+((p+2)^{n-1}-p^{n-1})

Thus p n + ( p + 2 ) n p n 1 + ( p + 2 ) n 1 = p + 1 + ( p + 2 ) n 1 p n 1 p n 1 + ( p + 2 ) n 1 \dfrac{p^n+(p+2)^n}{p^{n-1}+(p+2)^{n-1}}=p+1+\dfrac{(p+2)^{n-1}-p^{n-1}}{p^{n-1}+(p+2)^{n-1}}

Since p n 1 + ( p + 2 ) n 1 p n + ( p + 2 ) n p^{n-1}+(p+2)^{n-1}\mid p^n+(p+2)^n we must have that ( p + 2 ) n 1 p n 1 p n 1 + ( p + 2 ) n 1 \dfrac{(p+2)^{n-1}-p^{n-1}}{p^{n-1}+(p+2)^{n-1}} is an integer.

However, unless n = 1 n=1 at which ( p + 2 ) n 1 p n 1 p n 1 + ( p + 2 ) n 1 = 0 \dfrac{(p+2)^{n-1}-p^{n-1}}{p^{n-1}+(p+2)^{n-1}}=0 , the numerator, which is a positive integer, is always less than the denominator, which is also a positive integer.

Thus our only solution is 1 \boxed{1} .

Yep. Same solution here.

Dhruv Somani - 4 years, 1 month ago
Jubayer Nirjhor
Aug 15, 2014

Here's my solution.

Claim : Only n = 1 n=1 works.

We prove our claim in 3 3 steps. First we define f : N R f:\mathbb{N}\to\mathbb{R} by f ( n ) = p n + ( p + 2 ) n p n 1 + ( p + 2 ) n 1 f(n)=\dfrac{p^n+(p+2)^n}{p^{n-1}+(p+2)^{n-1}} for a fixed p N p\in\mathbb{N} .

Step 1 : We show that f ( n ) f(n) is increasing in [ 1 , ) [1,\infty) , that is, f ( n + 1 ) > f ( n ) f(n+1)>f(n) for all n N n\in\mathbb{N} . Letting p n 1 = x p^{n-1}=x and ( p + 2 ) n 1 = y (p+2)^{n-1}=y we have f ( n + 1 ) > f ( n ) p 2 x + ( p + 2 ) 2 y p x + ( p + 2 ) y > p x + ( p + 2 ) y x + y . f(n+1)>f(n)\implies \dfrac{p^2 x+(p+2)^2 y}{px+(p+2)y}>\dfrac{px+(p+2)y}{x+y}. Cross multiplying and cancelling gives p 2 + ( p + 2 ) 2 > 2 p ( p + 2 ) 4 > 0 p^2+(p+2)^2>2p(p+2)\implies 4>0 which is trivially true.

Step 2 : We bound the range of f f by computing the minimum and the maximum. Since f f is increasing, the minimum occurs at the minimum value of n n and the maximum occurs at the maximum value of n n in the domain.

So we have min f = f ( 1 ) = p + ( p + 2 ) 2 = p + 1 \min{f}=f(1)=\dfrac{p+(p+2)}{2}=p+1 . To compute the maximum, we let n n\to \infty :

lim n p n + ( p + 2 ) n p n 1 + ( p + 2 ) n 1 = lim n p ( p p + 2 ) n 1 + ( p + 2 ) ( p p + 2 ) n 1 + 1 = p + 2. \lim_{n\to\infty} \dfrac{p^n+(p+2)^n}{p^{n-1}+(p+2)^{n-1}}=\lim_{n\to\infty} \dfrac{p\left(\frac{p}{p+2}\right)^{n-1}+(p+2)}{\left(\frac{p}{p+2}\right)^{n-1}+1}=p+2. So the range of f f is [ p + 1 , p + 2 ) [p+1,p+2) .

Step 3 : Step 2 implies that f f can give only two integer values, p + 1 p+1 and p + 2 p+2 . Time to deal with them one by one.

If f ( n ) = p + 2 f(n)=p+2 , then p n + ( p + 2 ) n = ( p + 2 ) ( p n 1 + ( p + 2 ) n 1 ) p n 1 = 0 p^n+(p+2)^n=(p+2)\left(p^{n-1}+(p+2)^{n-1}\right)\implies p^{n-1}=0 which is absurd.

If f ( n ) = p + 1 f(n)=p+1 , then p n + ( p + 2 ) n = ( p + 1 ) ( p n 1 + ( p + 2 ) n 1 ) p^n+(p+2)^n=(p+1)\left(p^{n-1}+(p+2)^{n-1}\right) which after expanding and manipulating becomes p n 1 = ( p + 2 ) n 1 n 1 = 0 n = 1. p^{n-1}=(p+2)^{n-1}\implies n-1=0\implies n=1.

Therefore n = 1 n=\boxed{1} is the only solution over all such p p .

EDIT : A way more easier solution: Let x = p n + ( p + 2 ) n x=p^n+(p+2)^n and y = p n 1 + ( p + 2 ) n 1 y=p^{n-1}+(p+2)^{n-1} . Now notice that: x = ( p + 2 ) y 2 p n 1 x=(p+2)y-2p^{n-1} . If y x y\mid x then y 2 p n 1 y\mid 2p^{n-1} . Then y 2 p n 1 p n 1 ( p + 2 ) n 1 y\le 2p^{n-1}\implies p^{n-1}\geq (p+2)^{n-1} which is true only for n = 1 n=1 .

Let n 2 n\ge2

p n + ( p + 2 ) n = p^{n}+(p+2)^{n}=

( 2 p + 2 ) ( p n 1 + ( p + 2 ) n 1 ) ( p n 2 + ( p + 2 ) n 2 ) p ( p + 2 ) (2p+2)(p^{n-1}+(p+2)^{n-1})-(p^{n-2}+(p+2)^{n-2})p(p+2)

So p n 1 + ( p + 2 ) n 1 p ( p + 2 ) ( p n 2 + ( p + 2 ) n 2 ) p^{n-1}+(p+2)^{n-1}|p(p+2)(p^{n-2}+(p+2)^{n-2}) but unless p = 2 p=2 , this implies that p n 1 + ( p + 2 ) n 1 ( p n 2 + ( p + 2 ) n 2 ) p^{n-1}+(p+2)^{n-1}|(p^{n-2}+(p+2)^{n-2}) but that can't be true as a number can's divide anything smaller than itself .

Is the above proof correct?

Rahul Saha - 6 years, 10 months ago

Log in to reply

That is the official solution. Funnily enough, I solved it @Jubayer Nirjhor 's way.

Mursalin Habib - 6 years, 10 months ago

Yes, that's correct. This is the official solution to the problem that appeared in St. PCMO 1996.

Jubayer Nirjhor - 6 years, 10 months ago

Can't we generalize the problem further by saying that if a , b a,b are coprime positive numbers such that a n + b n a n + 1 + b n + 1 a^n+b^n|a^{n+1}+b^{n+1} ,then n = 0 n=0 ?

Rahul Saha - 6 years, 10 months ago

Log in to reply

Yes we can. But I don't think that they have to be coprime. The only condition we need is a b ( m o d 2 ) a\equiv b\pmod 2 .

Jubayer Nirjhor - 6 years, 10 months ago
Jesse Nieminen
Mar 15, 2017

p n 1 + ( p + 2 ) n 1 p n + ( p + 2 ) n p n 1 + ( p + 2 ) n 1 p n + ( p + 2 ) n ( p + 2 ) ( p n 1 + ( p + 2 ) n 1 ) p n 1 + ( p + 2 ) n 1 2 p n 1 ( p + 2 ) n 1 p n 1 n = 1 \quad \ p^{n-1} + \left(p+2\right)^{n-1} \mid p^n + \left(p+2\right)^n \\ \Leftrightarrow p^{n-1} + \left(p+2\right)^{n-1} \mid p^n + \left(p+2\right)^n - \left(p+2\right)\left(p^{n-1} + \left(p+2\right)^{n-1}\right) \\ \Leftrightarrow p^{n-1} + \left(p+2\right)^{n-1} \mid 2p^{n-1} \\ \Rightarrow \left(p+2\right)^{n-1} \leq p^{n-1} \\ \Rightarrow n = 1

Hence, the answer is 1 \boxed{1} .

Sanzeed Anwar
Aug 15, 2014

Let a b a|b denote that a a divides b b . Now [ p n 1 + ( p + 2 ) n 1 ] [ p n + ( p + 2 ) n ( p + 2 ) p n 1 + ( p + 2 ) ( p + 2 ) n 1 ] = 2 p n 1 [p^{n-1}+(p+2)^{n-1}]|[p^{n}+(p+2)^{n}-(p+2)p^{n-1}+(p+2)(p+2)^{n-1}]=-2p^{n-1} . So, [ p n 1 + ( p + 2 ) n 1 ] [ 2 p n 1 p n 1 ( p + 2 ) n 1 ] = p n 1 ( p + 2 ) n 1 [p^{n-1}+(p+2)^{n-1}]|[2p^{n-1}-p^{n-1}-(p+2)^{n-1}]=p^{n-1}-(p+2)^{n-1} . But p n 1 + ( p + 2 ) n 1 > p n 1 ( p + 2 ) n 1 p^{n-1}+(p+2)^{n-1}> p^{n-1}-(p+2)^{n-1} . Thus n 1 = 0 n-1=0 which gives us the only solution.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...